Surgical Care Required for Populations Affected by Climate-related Natural Disasters :A Global Estimation - Lee, Eugenia E. (2020)
Background: Climate extremes will increase the frequency and severity of natural disasters worldwide. Climate-related natural disasters were anticipated to affect 375 million people in 2015, more than 50% greater than the yearly average in the previous decade. To inform surgical assistance preparedness, we estimated the number of surgical procedures needed. Methods: The numbers of people affected by climate-related disasters from 2004 to 2014 were obtained from the Centre for Research of the Epidemiology of Disasters database. Using 5,000 procedures per 100,000 persons as the minimum, baseline estimates were calculated. A linear regression of the number of surgical procedures performed annually and the estimated number of surgical procedures required for climate-related natural disasters was performed. Results: Approximately 140 million people were affected by climate-related natural disasters annually requiring 7.0 million surgical procedures. The greatest need for surgical care was in the People’s Republic of China, India, and the Philippines. Linear regression demonstrated a poor relationship between national surgical capacity and estimated need for surgical care resulting from natural disaster, but countries with the least surgical capacity will have the greatest need for surgical care for persons affected by climate-related natural disasters. Conclusion: As climate extremes increase the frequency and severity of natural disasters, millions will need surgical care beyond baseline needs. Countries with insufficient surgical capacity will have the most need for surgical care for persons affected by climate-related natural disasters. Estimates of surgical are particularly important for countries least equipped to meet surgical care demands given critical human and physical resource deficiencies.